A step up with the HARVARD system: the HARVARD-g system - Ruy Ramos (2007)
The HARVARD system is a general purpose system adequate for Knowledge Discover in Databases (KDD) running in general purpose PCs and based on distributed computing over a connected network of PCs. In this paper we discuss the extension of HARVARD to interact with a Grid Computing setting. This extension, called HARVARD-g, enable the HARVARD system to schedule task to the Grid and therefore largely increase its available computational power.